Plant-based pharmacological alternatives in the seizure treatment: A patent review (Research, Society and Development, 2022)
Epilepsy, a neurologic condition associated with recurring seizures, affects around 70 million people worldwide and it is responsible for health costs. The current drug therapies used for treating epilepsy have low efficacy and many adverse side effects. In addition, drug resistance can also be found. The association of these factors considerably compromises the patient's pharmacotherapy care. Therefore, natural plant-derived products are promising therapeutic alternatives in the search for new curative options to treat epileptic seizures. Thus, the search was carried out at the patents database in the world, Espacenet, in January 2021 and compiled plant species (extracts, essential oils and isolated plant compounds) with a potential effect on the seizure, published between 2015 and 2020. In recent years, researchers and pharmaceutical companies have developed several methods for obtaining extracts, essential oils and purification of natural compounds, which have proven to be effective for the treatment of epileptic seizures in pre-clinical animal models. These findings hold potential promising for the treatment of epilepsy, especially for the management of drug-resistant, however, these reports are in their early stages and further studies need to be done for these compounds to be marketed.